Analysis of Stock Prices With Solvency as an Intervening Variable in Pharmaceutical Companies on the Indonesian Stock Exchange - Amarta, Ananda Wahyu; Suwaidi , Rahman Amrullah (East Asian Journal of Multidisciplinary Research, 2024)
The current global industrial sector development demands standardized regulations in reporting. Various industrial sectors consider these standards crucial for competitiveness, ensuring uniform information for readers and investors alike. One form of investment in the capital market is investment in stocks. According to the investment theory of low risk, low reward, or high risk, big return, investing in stocks truly entails considerable risks. For pharmaceutical businesses registered on the Indonesian Stock Exchange, to calculate stock price analysis with solvency as an intervening variable. The documentation method is the data collecting strategy used to gather data. The study's findings show that the stock prices of pharmaceutical companies are positively impacted by profitability, solvency, and activity ratios.